Affecting Factors Social Influence and Intention to Use on Gopay in Indonesia - Anthony Putera; Liliana Inggrit Wijaya (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of using Gopay e-money in Indonesia, which is influenced by perceived usefulness, perceived ease of use, compatibility, personal innovation, individual mobility, intention to use, and social influence. The development of information technology and current payment systems has encouraged the development of an electronic payment instrument known as Electronic Money. E-Money is very safe to use. Electronic money is divided into electronics money is divided into two types. First, chip-based electronics money in the form of cards, such as e-Money, Flazz, and Brizzi. The second type server-based electronics money. This type of electronic money is usually in the form of applications such as Gopay, OVO, Shoppe Pay, Dana, and LinkAja, where this electronic money makes transactions easier. Develop the previous research model by adding social influence variables. Data processing method using SEM. The study results show that all hypotheses are supported except for perceived ease of use on intention to use.